Pengaruh Model Kooperatif Tipe Numbered Head Together (NHT) Terhadap Hasil Belajar IPS Siswa - Ratu Nurramadhoan; Nurhasanah; Syafruddin (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
Learning outcomes are a tool to measure the extent to which students have mastered the material taught by the teacher. This study aims to determine the effect of the Numbered Head Together (NHT) cooperative model on Social Studies learning outcomes for fourth grade students at SDN Inpres Tambe in the 2021/2022 academic year. This research is a quantitative study with a nonequivalent control group design with a quasi-experimental type of design. The population in this study were all fourth grade students of SDN Inpres Tambe in the 2021/2022 academic year. The sample in this study was the fourth grade students of SDN Inpres Tambe as the experimental class and the fourth grade students of SDN 9 Sila as the control class. Data analysis begins with a normality test using the Kolmogorov Smirnov formula with a significance level of 5% (0.05) and continues with a homogeneity test, then tests the research hypothesis and further tests with an effect size test. Then the learning outcomes data were analyzed by t-test to determine the research hypothesis. The results of data analysis obtained a sig.2 tailed value of 0.029 which is less than 0.05, then based on the research hypothesis, if tcount> ttable (2.238>1.671) then Ho is rejected and Ha is accepted. This shows that there is an effect of the Type IV Numbered Head Together (NHT) cooperative model on the Social Studies Learning Outcomes of Fourth Grade Students of SDN Inpres Tambe in the 2021/2022 academic year. Furthermore, to see how big the influence of the Numbered Head Together (NHT) cooperative model on the Social Studies Learning Outcomes of Class IV SDN Inpres Tambe students, a follow-up test using effect size was carried out, so a score of 1.00 was included in the large category. The conclusion of this study is that the Numbered Head Together type cooperative model has a change in students' cognitive learning outcomes as seen from the Numbered Head Together learning process has a significant effect on student learning outcomes based on hypothesis testing, obtained sig.2 tailed of 0.029<0.05. The influence of the Numbered Head Together learning model on social studies learning outcomes is 1.00, which is included in the large category.